FASHION PRODUCT DESIGN INNOVATION AND DIGITAL MARKETING ON IKAT WEAVING ARTISANS IN GROBOGAN - M. Rudianto; Sarwono Sarwono; Noor Ismawati Binti Jaafar; Sujadi Rahmat Hidayat; Nisaul Hasanah A Rosyad; Rochmat Aldy Purnomo; Ratna Endah Santoso; Siti Arifah (Studi Kasus Inovasi Ekonomi, 2025)
The production of traditional ikat weaving in Lajer Village, Grobogan Regency, has produced woven fabrics as local creative products. There are issues related to limited design variety, production capacity, and marketing reach, which have resulted in market demand not being optimally met. This international community service program involves partners from the Syahadah Grobogan Cooperative Group (KUB), comprising young people and women from economically disadvantaged backgrounds. The program aims to improve product quality, expand the market, and increase revenue through training in innovative motif design, fashion product development, and digital marketing via e-commerce platforms. The implementation method includes presentations, hands-on practice, and ongoing mentoring. The results of the activities show an increase in technical skills and design creativity, understanding of modern production technology, and the use of digital media for promotion and sales. This program supports the achievement of the SDGs, particularly Goal 5 (Gender Equality), Goal 8 (Decent Work and Economic Growth), and Goal 9 (Industry, Innovation, and Infrastructure), and aligns with the President of the Republic of Indonesia's Nawa Cita vision for building economic self-reliance based on local potential.